Práticas de organizar na indústria criativa: a produção de um espetáculo de teatro musical em São Paulo - SP - Duarte, Márcia de Freitas (2015)
This thesis aims to understand the practices and actions of organising necessary for production /organization of a musical theatre show in São Paulo, in order to explore how materially heterogeneous relations and articulations sustain it and allow their presentations. The focus on practice and organising is aligned to the concern of Organizational Studies (OS) about how 'organizations happen' and in the understanding of the everyday organizational processes and practices, referring to the comprehension of organizations as a process (organizing) in constant state of (re)constitution. The literature in creative industries presents a lack related to the organization of creative goods or services, considering it focuses its attention more in the consumption of these products than in their organization or production. The notion of creativity is also pointed as just a human attribute, a talent or ability without emphasizing some creative or cultural goods or services only can happen or are produced considering the relations and actions between human and non-human elements. In organizational literature, theatre is studied as metaphor or as a sort of intervention/tool in processes of organizational changes or learning and not as a particular form of organization. Musical theatre, a creative industry, seems to be a consolidated activity in Brazil, mainly by the increase of large musical montages from Broadway shows and its increasing professionalization, particularly in the last decade and especially in São Paulo, SP. Its production differs from other theatrical genres by the number of professionals, the amount of investments and presence of technology highlighted in its sound, light and set design and stage management department, making it a fertile field for the exploration about how these actors get together and form the visible show (seen on the stage by the audience) and the invisible one (hidden behind the scenes). About this aspect, Actor-Network Theory (ANT), here used as theoretical and methodological framework , is an approach which provides an analytical repertoire for understanding the organization as the effect of a network of heterogeneous elements, with a stability temporarily achieved. This is a qualitative research and to achieve the aim of exploring the organization of a musical I carried out a fieldwork inspired in ethnographic principles along ten months in one company whose show was being presented in São Paulo between 2013 and 2014. From what was observed in the field, I described the associations and articulations between human and non-human actors, which are permeated by efforts to generate a stabilized order, even if precarious, which is here understood the musical itself (macro-actor or network-of-actors) and its more than three hundred performances during the season, resulting from actions in continuous (re)constitution. Negotiations concerning copyright acquisitions, particular aspects of the Portuguese language, the Brazilian audience, the bodies and voices of the Brazilian cast, the structural constraints of the theater, the production of documents, marking the rehearsing room, the articulation of the show via sound and image systems, the acquisition of specific equipment and the ‘calling system’ which allows to 'call the show' during the presentation are some of the themes I explored. In conclusion, with this research, I attempted to link the growing interest of OS field in relation to organising and some of the possibilities offered by ANT on the understanding of the multiplicity and heterogeneity inherent to organizational practices, in order to enrich the discussion of the organization and production of creative goods and services highlighting how the organization 'musical theatre show' is multiple and materially heterogeneous, and not only an idea related to human agency or creativity as production input, as emphasize the most descriptions related to creative industries.